Synthesis and controlled release properties of phenoxyherbicides-layered hydroxide nanohybrids - Hashim, Norhayati (2012)
Organic-inorganic nanohybrids of phenoxyherbicides, 4-(2,4-dichlorophenoxy)butyrate, 2(2,4-dichlorophenoxy)propionate and 3(2-chlorophenoxy)propionate into the interlayers of zinc-aluminium-layered double hydroxides have been synthesized using coprecipitation and ion exchange methods. PXRD patterns showed sharp, intense and symmetrical peaks which is due pure phase and good crystallinity of the nanohybrids prepared by both co-precipitation and ion exchange methods. Compositional studies showed the estimated percentage of phenoxyherbicides intercalated in the interlayer zincaluminium-layered double hydroxides are 53.9 % and 54.7 % of 4-(2,4-dichlorophenoxy)butyrate, 47.8 % and 58.5 % of 2(2,4-dichlorophenoxy)propionate,38.3 % and 42.3 % of 3(2-chlorophenoxy)propionate that synthesized using coprecipitation and ion exchange methods, respectively. FTIR and thermal analysis supported that phenoxyherbicides was successfully intercalated into the Zn/Al-layered double hydroxides. A release study of phenoxyherbicides from interlayer nanohybrid was carried out in various concentrations of sodium chloride, sodium carbonate and sodium phosphate and the mixture of sodium chloride, sodium carbonate and sodium phosphate aqueous solutions. Controlled release study of phenoxyherbicides into the aqueous solutions is in order of: 3(2-chlorophenoxy) propionate > 2(2,4-dichlorophenoxy) propionate > 4-(2,4-dichlorophenoxy)butyrate. The accumulated release percentage of phenoxyherbicides into aqueous solutions is in order of: sodium carbonate > sodium phosphate > sodium chloride. The kinetic study showed that pseudo-second order was the best model to describe almost all the release profiles of the phenoxyherbicides anion from Zn/Al-phenoxyherbicides nanohybrid. A new layered organic-inorganic nanohybrid material containing an agrochemical, 4-(2,4-dichlorophenoxy)butyrate and 3(2-chlorophenoxy)propionate in the interlayer of zinc-layered hydroxide was also accomplished by direct reaction of aqueous phenoxyherbicides solution with zinc oxide. The nanohybrids showed well ordered crystalline layered structure, a basal spacing of 29.6 Å and 22.7 Å, and percentage loading of 47.9 % and 38.8 % of 4-(2,4-dichlorophenoxy)butyrate and 3(2-chlorophenoxy)propionate, respectively. FTIR study possessed that the absorption bands characteristics of both the phenoxyherbicides and zinc-layered hydroxide which is confirmed the intercalation process. The release study of the phenoxyherbicides into the aqueous solutions of sodium chloride, sodium carbonate and sodium phosphate showed higher accumulated percentage release of 3(2-chlorophenoxy)propionate compared to 4-(2,4-dichlorophenoxy)butyrate. Release of phenoxyherbicides into the aqueous solutions is in order of: sodium carbonate > sodium phosphate > sodium chloride. The release of 4- (2,4-dichlorophenoxy)butyrate and 3(2-chlorophenoxy) propionate from their nanohybrids was also done into a mixture of solution sodium chloride, sodium carbonate and sodium phosphate. The results of the release profile showed high accumulated release of both phenoxyherbicies anion into the solution containing carbonate or mixture of carbonate and phosphate. The kinetic behaviour of both phenoxyherbicides release from its nanohybrid are also agree well with the parabolic diffusion release model. This study showed that the formation of organic-inorganic nanohybrid materials of, 4-(2,4-dichlorophenoxy)butyrate, 2(2,4-dichlorophenoxy)propionate and 3(2-chlorophenoxy) propionate anions as organic guests and zinc-aluminum-layered double hydroxide and zinc layered hydroxide as hosts were successfully synthesized.4-(2,4-dichlorophenoxy) butyrate showed the highest percentage intercalation into the interlayer layered metal hydroxide material as shown percentage loading as compared to 2(2,4-dichlorophenoxy) propionate and 3(2-chlorophenoxy)propionate anion. The release of phenoxyherbicides from the matrix revealed that the zinc-aluminium layered double hydroxide and zinc layered hydroxide can be potentially used as a host for controlled release formulation.